Tides of Innovation in Oceania: Value, materiality and place - Gnecchi-Ruscone, Elisabetta; Paini, Anna (ANU Press, 2017)
Tides of Innovation in Oceania is directly inspired by Epeli Hau'ofa's vision of the Pacific as a 'Sea of Islands'; the image of tides recalls the cyclical movement of waves, with its unpredictable consequences. The authors propose tides of innovation as a fluid concept, unbound and open to many directions. This perspective is explored through ethnographic case studies centred on deeply elaborated analyses of locally inflected agencies involved in different transforming contexts. Three interwoven themes-value, materiality and place-provide a common thread.